Paleotopographic controls on loess deposition in the Loess Plateau of China. Issue 9 (5th January 2016) - Xiong, Li‐Yang; Tang, Guo‐An; Strobl, Josef; Zhu, A‐Xing
Abstract: The underlying pre‐existing paleotopography directly influences the loess deposition process and shapes the morphology of current loess landforms. An understanding of the controlling effects of the underlying paleotopography on loess deposition is critical to revealing the mechanism of loess‐landform formation. However, these controlling effects exhibit spatial variation as well as uncertainty, depending on a study's data sources, methodologies and particular research scope. In this study, the geological history of a study area in the Loess Plateau of China that is subject to severe soil erosion is investigated using detailed geological information and digital elevation models (DEMs), and an underlying paleotopographic model of the area is constructed. Based on the models of modern terrain and paleotopography, we introduce a watershed hierarchy method to investigate the spatial variation of the loess‐landform inheritance relationship and reveal the loess deposition process over different scales of drainage. The landform inheritance relationships were characterized using a terrain‐relief change index (TRCI) and a bedrock terrain controllability index (BTCI). The results show that the TRCI appears to have an inverse relationship with increasing research scope, indicating that, compared with the paleotopography of the region, modern terrain has lower topographic relief over the entire area, while it has higher topographic relief in the smaller, local areas. The BTCI strengthens with increasing drainage area, which demonstrates a strong controlling effect over the entire study area, but a weak effect in the smaller, local areas because of the effect of paleotopography on modern terrain. The results provide for an understanding of the spatial variation of loess deposition in relation to paleotopography and contribute to the development of a process‐based loess‐landform evolution model. Copyright © 2015 John Wiley & Sons, Ltd.